Hydrocele of the Nuck canal - Lohourou Grah Franck; Kpangni Ahua Jean Bertrand; Bénié Adoubs Celestin; Traoré Ibrahim; Bony Ursula Constance; Traoré Abdoul Massandje; Tumameu Thierry; Kouadio Kouadio Narcisse (Elsevier, 2023)
The process vaginalis in the inguinal canal forms the canal of Nuck, which is a homolog of the process vaginalis in women. Incomplete obliteration of the vaginal process causes an indirect inguinal hernia or hydrocele of the canal of Nuck, a very rare condition in women. A hydrocele of the Nuck canal, although rare, should be considered in the differential diagnosis in girls with inguinal swelling. Establishing a definitive diagnosis on physical examination is difficult, radiological imaging can help diagnosis, but surgical exploration is essential for the final diagnosis. The authors report a case of congenital hydrocele in a 2-year-old girl and review the literature on this rare entity whose diagnosis can be made by surgical exploration.